In vitro anti-oxidation activity studies of the whole plant (except flower) of Thunbergia coccinea - Damanbhalang Rynjah; Sumit Das (Creative Pharma Assent, 2020)
An in vitro study of the methanolic extract of the whole plant (except flower) of Thunbergia coccinea was performed to check the anti-oxidant activity by different methods (Reducing power assay, TBA and DPPH scavenging assay) and before starting the study, the plant was extracted by Soxhlet apparatus using methanol as solvent and the marc was evaporated kept under desiccator. From the literature survey it was found that the plant contain flavonoids and tannins which are non-enzymatic antioxidants responsible for scavenging free radicals as reported and based on this, the study for antioxidant was carried out. The methanolic extract of the plant Thunbergia coccinea shows promising result in antioxidant studies when in comparison with the standard (Ascorbic acid). Thus further studies like in vivo evaluation can be performed in the mere future.